A Web-Based Interface For A High Performance Computing System - Awad, Mohammed M. I. (2008)
High performance computing systems (HPCS) target to execute software whether this software is a simple or complicated one. Most of HPCS should have an interface to enable software owners to upload their files to be installed by the HPCS administrator. The interface should be extensible to work together in the future with the other remaining parts of the complete system. Also it has to be divided into phases in order to make development easier and also to make those components reusable. It is the best option to make the software a platform independent one. To achieve that, J2EE (Java 2 Enterprise Edition) should be chosen to implement this interface and also free licensed and open source software have to be chosen such as Tomcat Jakarta server, MySQL to be used in the development phases. All of the previous recommendations are applied in this research prototype. On top of that, the interface prototype has been tested on local environment and has achieved the expected results. This report passes through all phases to have a proper web interface to be used for a HPCS.